Vida Saludable: Cambiando su estilo de vida para mejorar su presión arterial - Karla P. Shelnutt (EDIS)
FCS8885-Span, a 2-page fact sheet by Karla P. Shelnutt, is the Spanish language version of FCS8885/FY1129 Healthy Living: Changing Your Lifestyle to Improve Your Blood Pressure. It highlights some lifestyle changes that can help control or prevent high blood pressure — losing weight, increasing physical activity, limiting alcohol consumption, and stopping smoking. Published by the UF Department of Family Youth and Community Sciences, November 2009.